Criteria and considerations in feasibility studies of reservoirs (Revista de Investigaciones Universidad del Quindío, 2010)
Water is a scarce resource and essential for the various activities of the people. The water uses generate demand for the precious water resources within a watershed. Likewise, each river basin has a water supply that often turns out to be inferior to the demands of water and is in this situation as a resource waterworks such as dams, reservoirs, dams, among others to mitigate the demand on a limited water supply. The reservoirs are an essential element for the regulation of water resources and contribute very significantly to human progress. This article discusses some technical, economic, social and environmental issues that are important to highlight in the design of hydraulic projects such as a reservoir. The purpose is to guide and give evidence to the general public and especially to remember those elements of decision makers in regard to the screening and feasibility studies for construction of a dam in a certain region. As a case study explores the possibility of a dam on the Department of Quindio, located in the coffee region of Colombia, a situation that has generated different expectations and uncertainties in much of the population of the region.
Keywords: Reservoir; water uses; planning and management of water resource